2021
DOI: 10.3390/agronomy11101969
|View full text |Cite
|
Sign up to set email alerts
|

Prospects for Use of Biological Control of Insect and Mites for the Food Industry in North America

Abstract: There are a number of strategies used to mitigate and control insect infestations in stored products and stored product facilities in North America and globally. Fumigation remains one of the main techniques used, particularly in bulk grain. Other techniques are also utilized effectively, such as the use of extreme temperatures and the use of biological control agents, but are mainly restricted to organic products and to Europe, respectively. Here, we review the past research conducted in the field of biologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…Natural enemies of pests can reduce their populations below an economic threshold level, especially in isolated environments such as greenhouses (Pijnakker et al, 2020 ), and the use of parasitic wasps against stored‐product pests in granaries holds similar promises (Hervet & Morrison III, 2021 ). The biocontrol efficiency of a number of predators and hymenopteran parasitoids has been assessed.…”
Section: Discussionmentioning
confidence: 99%
“…Natural enemies of pests can reduce their populations below an economic threshold level, especially in isolated environments such as greenhouses (Pijnakker et al, 2020 ), and the use of parasitic wasps against stored‐product pests in granaries holds similar promises (Hervet & Morrison III, 2021 ). The biocontrol efficiency of a number of predators and hymenopteran parasitoids has been assessed.…”
Section: Discussionmentioning
confidence: 99%
“…Biological control may be useful to incorporate into the current management program because this tactic may provide a safe, sustainable method of P. casei management without the issues brought on by reliance on insecticides ( Rossi and Presciuttini 1996 , Fields and White 2002 , Schöller 2010 , Russo 2011 ). Concerns have been raised about potential food contamination by arthropods (e.g., biological control agents), regulations that prohibit the sale of contaminated food products, and negative consumer and processor perceptions ( Hervet and Morrison 2021 ). However, studies conducted in the management of other stored product arthropod pests have shown that use of parasitoids to control the pest did not result in an increase in the arthropod fragments in the stored products ( Flinn and Hagstrum 2001 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, studies conducted in the management of other stored product arthropod pests have shown that use of parasitoids to control the pest did not result in an increase in the arthropod fragments in the stored products ( Flinn and Hagstrum 2001 ). Any remaining arthropod fragments could be removed from the stored products using standard cleaning procedures ( Hervet and Morrison 2021 ).…”
Section: Introductionmentioning
confidence: 99%